[12]aneN3-Conjugated AIEgens with two-photon imaging properties for synergistic gene/photodynamic therapy in vitro and in vivo. Issue 6 (24th January 2022) - Liu, Xu-Ying; Yang, Jing-Bo; Wu, Cheng-Yan; Tang, Quan; Lu, Zhong-Lin; Lin, Lan
Abstract : Six amphiphiles consisting of macrocyclic polyamine triazole-[12]aneN3  (M ) and tetraphenylethenethiophene modified cyanoacrylate (TTC ) moiety linked with alkyl chains (L ), have been synthesized for synergetic anticancer gene therapy and photodynamic therapy. Abstract : Six amphiphiles (TTC-L-M-1/2 /3 /4 /5 /6 ), each consisting of hydrophilic macrocyclic polyamine triazole-[12]aneN3 (M ) and a hydrophobic photosensitizer tetraphenylethenethiophene modified cyanoacrylate (TTC ) moiety linked with alkyl chains (L ), have been designed and synthesized for synergetic anticancer gene therapy and photodynamic therapy (PDT). These amphiphiles showed strong AIE fluorescence emissions around 600 nm with large Stokes shifts up to 168 nm in an aqueous solution. They were able to condense DNA into nanoparticles with appropriate sizes, positive charges, reversible release, and good biocompatibility. Quantitative and qualitative gene transfection studies indicated that TTC-L-M-4 with a 12 carbon alkyl chain exhibited the best transfection efficiency in HeLa cells, and its transfection efficiency was 4.5-fold that of Lipo2000 in the presence of DOPE. The detailed and efficient delivery process of DNA by TTC-L-M-4 was clearly observed through one- and two-photon fluorescence imaging. Simultaneously, TTC-L-M-4 /DOPE was able to deliver siRNA and gene silencing was better than that of Lipo2000. Furthermore, TTC-L-M-4 was able to efficiently generate reactive oxygen species (ROS) for PDT upon light irradiation. It was further demonstrated that combined p53 gene therapy and PDT significantly enhanced cancer therapy in vitro and in vivo . This study provides novel one-for-all organic agents with multiple therapeutic modalities.